Ethical Risks of Social Experiments in Medical Artificial Intelligence and Its Governance Pathways - Xue YU; Bohan LIU (Yixue yu zhexue)
In the process of integrating medical artificial intelligence (AI) with real-world medical scenarios, the disruptive features of AI bring a series of ethical risks. Therefore, it is necessary to conduct social experiments in medical scenarios and continuously monitor the ethical risks they may cause. Currently, social experiments involving medical AI have been applied to several specific scenarios, but in the specific conduct of the experiments, there are still ethical risks in terms of experimental objects, elements, and benefits, which urgently require ethical governance. In terms of ethical governance, researchers should adhere to the principles of autonomy, non-maleficence, beneficence, and justice under the premise of protecting human well-being. Ethical governance should be standardized by protecting the rights and interests of experimental subjects, strictly defining inclusion and exclusion criteria, and comprehensively assessing experimental benefits. Specific governance measures should integrate ethical supervision, ethical review, and ethical management.